ARBITRATION UNDER THE AFRICA CONTINENTAL FREE TRADE AGREEMENT: STRENGTHENING TRADE DISPUTE RESOLUTION IN AFRICA - Madaki, Agbo Johnson (ABUAD Private and Business Law Journal, 2019)
The Africa Continental Free Trade Agreement (AfCFTA) represents a groundbreaking effort to promote regional economic integration and trade facilitation within the African continent. The agreement was adopted by African Union member States in March 2018, and after the ratification process was completed by the required number of countries, it entered into force on May 30, 2019. With the operationalization of the AfCFTA, disputes among member States and other parties are inevitable. To ensure effective resolution of these disputes, the AfCFTA – Dispute Settlement Mechanism Protocol offers three broad dispute resolution options. This article explores the arbitration provisions under the AfCFTA, evaluates their potential strengths, challenges, and offers recommendations for strengthening the arbitration framework within the trade agreement. Capacity-building initiatives will empower stakeholders to engage effectively in arbitration proceedings, while promoting diversity and inclusivity in arbitrator appointments will instill confidence in the fairness of the process. Increased transparency and public awareness will foster trust and wider utilization of arbitration, while collaboration with established arbitration institutions will enrich the AfCFTA dispute resolution practices.